Planning and Evaluation of Social Media Content for the Dissemination of Chinese Culture - Diana Trivena Yulianti; Adelia Adelia; Hendra Bunyamin; Theo Agathos; Willianson Willianson (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
The strategy of planning and evaluating social media content for disseminating Chinese culture aims to enhance public understanding and appreciation of Chinese cultural heritage in Indonesia. In today's digital era, social media serves as a powerful tool to communicate cultural values and reach a wide audience effectively. This study focuses on designing a structured content strategy that includes planning, creating, and distributing cultural content tailored to audience preferences. It also emphasizes the importance of continuous evaluation through analytics provided by social media platforms to measure engagement, reach, and user interaction. The research employs a qualitative approach involving observation, content analysis, and engagement metrics to identify what types of content resonate most with users. By analyzing trends, audience demographics, and feedback, the study reveals that creative and contextually relevant content—such as visual storytelling, interactive posts, and culturally themed campaigns—significantly improves user engagement. The findings highlight that incorporating elements such as localization, cultural narratives, and user-generated content contributes to a more meaningful connection between the audience and Chinese cultural heritage. Furthermore, the study demonstrates that strategic use of social media not only increases visibility but also fosters cultural appreciation among diverse communities in Indonesia. The implications of this research can be applied to broader digital cultural promotion efforts, offering practical guidance for institutions, cultural organizations, and educators seeking to communicate heritage through modern platforms. Ultimately, this study provides a model for using digital media strategically to support cross-cultural understanding and the sustainable promotion of cultural identity.